Collective impact: dialogue at the interface of the colliding systems of philanthropy. (21st February 2020) - Yawson, Robert M.; Peterson, Gayle; Johnson-Kanda, Ivy
Collective impact as a collaborative effort arose from the acknowledgement that existing methods and development approaches were incapable of addressing large-scale and long-term societal problems, the so-called wicked problems. By creating a model of the ecosystem of organisations around a particular issue, a funder can understand who else is working in the same space, identify potential allies, and anticipate political or economic challenges that might arise. In a case study to assess the developmental impacts of foreign aid and developmental programs on women and children in one of the poorest districts in Ghana, we developed an approach through which collective impact can be initiated and evaluated. Through the life of Lamisi Seidu, a typical, poor, rural Ghanaian woman, we tell the symbolic story of poor women living in rural, peri-urban, and urban areas all over the world. We examine what defines collective impact, how such initiatives are structured, and the challenges in creating collective impact initiatives that achieve successes that are both long lasting and large scale. We also discuss the landscape mapping approach we developed.